Haploinsufficiency of CUX1 Causes Nonsyndromic Global Developmental Delay With Possible Catch‐up Development. Issue 2 (31st August 2018) - Mitter, Diana; Lemke, Johannes R.; Platzer, Konrad; Jamra, Rami; Ploos van Amstel, Hans K.; van der Smagt, Jasper J.; Stegmann, Alexander P.A.; Stumpel, Constance T.R.M.; Stevens, Servi J.C.; Oberndorff, Katrin; Marcelis, Carlo L.; Cogné, Benjamin; et al.
Abstract : Objective: Developmental delay (DD) with favorable intellectual outcome and mild intellectual disability (ID) are mostly considered to be of complex genetic and environmental origin, but, in fact, often remain unclear. We aimed at proving our assumption that also mild cases of DD and ID may be of monogenic etiology. Methods: We clinically evaluated 8 individuals and performed exome sequencing or array copy number analysis and identified variants in CUX1 as the likely cause. In addition, we included a case from the public database, DECIPHER. Results: All 9 individuals harbored heterozygous null‐allele variants in CUX1, encoding the Cut‐homeobox 1 transcription factor that is involved in regulation of dendritogenesis and cortical synapse formation in layer II to IV cortical neurons. Six variants arose de novo, while in one family the variant segregated with ID. Of the 9 included individuals, 2 were diagnosed with moderate ID, 3 with mild ID, and 3 showed a normal age‐related intelligence at ages 4, 6, and 8 years after a previous history of significant DD. Interpretation: Our results suggest that null‐allele variants, and thus haploinsufficiency of CUX1, cause an isolated phenotype of DD or ID with possible catch‐up development. This illustrates that such a developmental course is not necessarily genetic complex, but may also be attributed to a monogenic cause. Ann Neurol 2018;84:200–207